Solve the following linear equations : 5. 4(2y- 13) – 9(y-3) + 2 (3y – 10) = 0​

Question

Solve the following linear equations :
5. 4(2y- 13) – 9(y-3) + 2 (3y – 10) = 0​

in progress 0
Luna 2 weeks 2021-09-09T12:30:34+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-09T12:32:06+00:00

    Step-by-step explanation:

    4(2y - 13) - 9(y - 3) + 2(3y - 10) = 0 \\  \\ 8y - 52 - 9y + 27 + 6y - 20 = 0 \\  \\ 5y - 45 = 0 \\  \\ 5y = 45 \\  \\ y = 9

    hope it helps…..❤❤

    mark it as brainliest ……✌✌

    0
    2021-09-09T12:32:20+00:00

    Answer:

    we have to find the value of y

    4(2y – 13) – 9(y- 3) + 2(3y – 10) = 0

    8y – 52 – 9y + 27 + 6y – 20 = 0

    5y – 45 = 0

    y = 45/5

    y = 9

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )